Reconsidering Some of the Earth’s Biophysical Limits to the Long Term Sustainable Development of Humanity - Harizaj, Pëllumb R. (Journal of Environmental Accounting and Management, 2026)
Humans’ existence as living organisms depends on some essential natural resources and ecosystem services. On the other side, nature has a certain speed of regenerating its resources required by hu- mans. Therefore, the consumption rate of natural resources by soci- ety should be equal to or slower than the nature’s speed of resource recovery in order to avoid overexploitation or degradation. This requires the quantitative definition of the Earth’s bio-physical limits that are crucial for the existence of human life, and monitoring of these limits by identifying the proper indicators of the Earth’s per- formance. A new economic theory designed according to the knowledge offered by pure and applied science might play a key role in achieving the long term sustainability goals of humanity.